Electronic cigarette use in Saudi Arabia: a cross-sectional study on emerging trends and public health concerns - Alhomoud, Farah Kais; Almuhayshi, Ayat; Altarouti, Roqaia; Abushaheen, Tuqa; Alhomoud, Faten; Alotaibi, Noor; Alsugeir, Dana; Alamer, Khalid A.; Alqarni, Yousef; Alfageh, Basmah; Almoghirah, Hailah; Alsulami, Fahad (Frontiers in Public Health, 2025)
BackgroundElectronic cigarette (e-cigarette) use has become increasingly popular worldwide, including in Saudi Arabia, especially among younger individuals. This study investigates the patterns, motivations, and perceptions of e-cigarette use to inform public health interventions and policy.MethodsThis descriptive cross-sectional study surveyed traditional cigarette smokers and ex-smokers above 18 in Saudi Arabia using an online questionnaire distributed via social media with convenience and snowball sampling. The tool, adapted from validated sources and refined through expert review and pilot testing, captured demographic data, smoking behaviors, perceptions, motivations, and patterns of e-cigarette use. Closed-ended questions ensured consistency in responses. A power analysis was conducted to determine the required sample size. Descriptive statistics, chi-square tests, one-way ANOVA, correlation analyses, and multinomial logistic regression were applied (p ≤ 0.05).ResultsFindings revealed that e-cigarette use was significantly higher among younger males (p = 0.028), with 86% of participants being male and 63% aged 18–28. Socioeconomic factors such as lower income and education levels were associated with higher usage rates (p = 0.001 and p = 0.030, respectively). Dual users of e-cigarettes and traditional cigarettes made up 47% of participants, while 31% were ex-smokers, and 22% were exclusive e-cigarette users. A preference for high nicotine content (≥16 mg) was noted among 26% of participants, and 44% reported adverse effects like shortness of breath and chest pain. Key motivations included smoking cessation (45%), flavor variety (35%), and perceived safety (29%). Retailers (43%) and online stores (27%) were the primary sources. Notably, 61% of participants supported government regulation of e-cigarettes. Gender, region, marital status, and education were significant predictors of usage patterns (p < 0.05).ConclusionsE-cigarette use is widespread among younger males in Saudi Arabia, driven by socioeconomic factors and perceptions of safety. Despite these perceptions, adverse effects like shortness of breath and chest pain were frequently reported. Comprehensive public health measures, including nicotine regulation, sales restrictions, taxation, and education, are urgently needed. Collaboration between the health and education sectors, along with continuous monitoring and research, is crucial for guiding effective national strategies.